COMPARATIVE BACTERICIDAL ACTIVITIES OF BLOOD SERUM AND PLASMA SERUM - Hirsch, James G. (The Rockefeller University Press, 1960)
Rabbit and human plasma can be prepared without resort to anticoagulants by employing low temperatures and non-wetting surfaces. Serum formed after clotting of rabbit plasma devoid of cells and platelets manifests essentially no bactericidal activity on Bacillus subtilis, Bacillus megaterium, and a strain of Staphylococcus aureus. In contrast, rabbit blood serum exhibits this activity to a high degree. Rabbit plasma rich in platelets gives rise to a serum with capacity to kill these Gram-positive microbes equal to that of serum prepared from whole blood. This heat-stable antibacterial agent is efficiently formed or released when platelets are present during the coagulation of plasma, but not on incubation of platelets in heparinized or citrated plasma or in saline. Leucocytes and red cells appear to play no significant role in its production. Rabbit blood serum and plasma serum have similar heat-labile lethal effects on enteric bacilli. Human serum, whether from blood or plasma, manifests much less bactericidal activity on Bacillus subtilis than does rabbit blood serum. These findings serve to emphasize the fact that substances formed or released during coagulation of whole blood may impart to the serum activities not present in circulating plasma.